The Analysis of Inclusive Green Growth In Indonesia - Aminata, Jaka; Nusantara, Dzulfikar Ilham Kusuma; Susilowati, Indah (Universitas Muhammadiyah Yogyakarta, 2022)
The concept of economic growth that has increased social welfare needs to be expanded in terms of its meaning and benchmarks. It focuses not only on economic activities but also on how they impact all of society in the present and the future. This study aims to analyze Indonesia’s inclusive green growth in 2015 and 2019. The method used to obtain the analysis is the Inclusive Green Growth Index (IGGI), conducted by Asian Development Bank (ADB). IGGI is a composite index consisting of three pillars: economic growth, social equity, and environmental sustainability. The study showed that Indonesia’s inclusive green growth was getting better where its average score in 2015 was 3.21, increasing to 3.36 in 2019. However, the improvement is not ideal yet because its mainly influenced by the economic growth pillar. In contrast, the average score of the environmental sustainability pillar declined from 4.19 in 2015 to 4.00 in 2019, accompanied by the decreasing social equity pillar score in 15 out of 34 provinces. All Efforts to achieve a better-balanced IGGI are improving and maintaining environmental quality, improving access to economic and political activities, improving public service and infrastructure in various provinces, and increasing superior and potential sectors to pursue economic disparity inter-provincial.